ISOKINETIC PROCEDURE ON SHOLDER MULDIRECTIONAL INSTABILITY (Fiep Bulletin - online, 2015)
This observational and descriptive study used the Isokinetic Dynamometry on subjects with Bilateral Multidirectional Instability of shoulder as physiotherapy treatment. It focused assessing and treating through strengthening the dynamic coaptator musculature of the shoulder, external rotators (ER) and internal rotators (IR), seeking greater stability for the joint. This study quantified such variables: Torque peak (TP) in (N.m), Total Work (TW) in joules and the Relations ER/IR (ER/IR), showing the width of the movements and angularities associated to the pain. A protocol of isokinetic treatment, made up of 24 sections and three assessments, was applied: initial, intermediate and final. This protocol for muscular strengthening of the ER and IR of the shoulder was applied on four female patients, average age 25, right-handed dominancy, being eight shoulders treated applying an average of 10 episodes of subluxations, and that undergone a conventional physiotherapy procedure without any improvement of the clinical picture. The results showed a better performance of the ER and IR along with all the arc of movement long. Therefore, getting better the ER and IR, reaching meaningful results for recuperation of the TP and TW during all width of movement of these two muscular groups. The ER/IR had a meaningful performance (p
Keywords: Isokinetic; Subluxation; Multidirectional Instability; Shoulder